PREVALENCE AND FACTORS ASSOCIATED WITH CARE DEPENDENCY OF CANCER PATIENT UNDERGOING CHEMOTHERAPY - Muhamad Zulfatul A'la; Rondhianto Rondhianto; Jon Hafan Sutawardana; Lianawati Lianawati (Jurnal Kesehatan Tambusai, 2023)
Increasing the number of cancer patients need exploration of the impact of cancer and chemotherapy. Care dependency is one impact of chemotherapy treatment and can affect the quality of life. Therefore, the prevalence and factor associated with care dependency of cancer patients undergoing chemotherapy need to be explored. This study aimed to determine the prevalence of care dependency and correlation among depression, hemoglobin level, pain, and fatigue to care dependency of cancer patients undergoing chemotherapy. Cross-sectional study was performed. 388 cancer patient undergoing chemotherapy in Baladhika Husada Hospital Jember, Indonesia was recruited using a consecutive sampling technique. Multivariate logistic regression was used to determine the association..The age of the samples was 51.49 (± 9.71) years old. This study found 29.9% of people have care-dependent conditions. After multivariate analysis, hemoglobin, pain, fatigue, and depression were statistically significant with care dependency. Conclusion: Fatigue has the most significant influence on care dependency of cancer patients undergoing chemotherapy. Further research needs to be analyzed care dependency in cancer patients using multi-center chemotherapy service. Also, the development of nursing interventions to reduce care-dependent conditions needs to be conducted.